Factors influencing the psychology and quality of life in lung cancer patients - Wang, Bin (Saudi Med J, 2017)
OBJECTIVES: To determine the factors closely correlated with the unhealthy psychological status of patients with lung cancer and to ascertain whether the unhealthy psychology adversely affects their quality-of-life (QOL). METHODS: Patients newly diagnosed with lung cancer between May 2013 and December 2015 in the Department of Thoracic Surgery, Tianjin 4th Centre Hospital, Tianjin, China were enrolled in this cross-sectional study. Patients were asked to complete the Symptom Checklist 90 (SCL-90) and Quality of Life Questionnaire (QLQ-C30) survey. From the responses, the correlation between the patient’s psychological status and QOL were analyzed with respect to several variables. RESULTS: From the total of 258 patients subjected to the test, 168 belonged to the unhealthy psychology group and 90 to the healthy psychology group. Multiple regression analysis revealed that significant factors related to poor QOL among the 2 groups are gender (p=0.02), younger age (p=0.001), surgical history (p=0.04), employment status (p=0.03), and medical insurance (p=0.01) significantly predicted the severity of unhealthy psychology in lung cancer patients. A significantly negative correlation was noted between the points of SCL-90 and the general QOL in all included patients (p=0.03). CONCLUSION: Gender, younger age, surgical history, employment status, and medical insurance significantly predicted the severity of unhealthy psychology in lung cancer patients.